Group counseling and students with attention deficit hyperactivity disorder (ADHD) an exploratory study - Ilmedo, Celeste C. (2009)
Attention Deficit Hyperactivity Disorder (ADHD) is a condition that becomes evident in some children in preschool. The research tried to look for an alternative means to address the needs of these children to cope with the disorder. Group counseling was conducted on eight male elementary students with ADHD using a single-group pretest-posttest design. VAS was administered before and after the series of group counseling with the respondents. Wilcoxon-signed rank test was used to determine if the group counseling sessions made a difference in their behavior. The result showed that there was a difference in the behavior of children with ADHD before and after exposing them to group counseling. It was concluded that group counseling is an effective intervention in order to improve the conditions of individuals with ADHD.